Development of effective water treatment technique using calcerous skeleton stabilizing agent for attenuation of cadmium and lead ions - Lim, Ai Phing (2014)
Heavy metal pollution in the environment has become a great public concern globally due to the adverse effects to human health as well as flora and fauna. Various efforts have been taken to reduce the metal contamination level in the environment through controlling and remediation process. Conventional treatment process requires extra procedure to further remove the metal ions in the wastewater in order to produce safe quality of treated water. The thesis discusses on the removal of metal ions; cadmium, Cd (II) and lead ions, Pb (II), by using dead calcerous skeletons (CS) based on batch and column systems. In general, the study aimed to provide potential adsorbent for the removal of metal ions in consideration to the current wastewater treatment techniques. The removal efficiency, adsorption capacity and behaviors of adsorbents were examined during the metals removal process and incorporated with isotherm models. In the batch study, the removal of Cd (II) and Pb (II) ions by CS were evaluated by varying the contact time, adsorbent size, dosage, solution pH, and initial metal concentration. While, for the column study, the factors of adsorbent bed height, influent flow rate and initial concentrations were evaluated to obtain the removal performance of CS in continuous flow system. The results showed that the surface characteristics of CS did not significantly affected the removal efficiency of CS. The dosage requires for optimum removal of Cd (II) and Pb (II) ions in batch system were in minimal amount since the increased of dosage did not show significant increased in removal (p>0.05). The acidic solutions were observed to shift to neutral and alkali condition after equilibrated with CS due to the content of calcium carbonate (CaCO3) of CS. The adsorption capacity of CS has increased with high loading of metal ions which reveal that the CS were able to remove high concentration of Cd (II) and Pb (II) ions. Based on the isotherm models, the results demonstrated that the data were more favorable to Freundlich isotherm which indicated the adsorption process occurred in heterogeneous surface rather than monolayer. In the column study, the column with long bed height showed no exhaustion occurred during the continuous flow system as there was no breakthrough of 0.05 Ceff/Co (ratio of effluent concentration to influent concentration). The columns were able to operate more than 24 hours with double dose of CS to the shortest bed height which showed that the ability of CS to withstand high metal ions for long duration of operation. The column models were strongly correlated to the experimental data and well-presented the long bed columns. The PHREEQC model predicted the dissolution of CS which contributed to the increased of pH and calcium ions in the treated solutions. The adsorption and ion-exchange process between the CS and metal ions were also confirm by the formation of otavite and cerussite from Scanning electron microscope (SEM) and X-ray diffraction (XRD) analysis. Thus, this study provides potential materials for application in wastewater treatment system. The outcome of the study also reveals possible application for the treatment of acidic wastewater with high metals loading.